DETECTION OF MATERNAL ANTIBODY AGAINST RABIES IN PUPPIES IN BERINGKIT TRADITIONAL MARKET - Suardana, Ida Bagus Kade; Winaya, Ida Bagus Oka; Agustina, Kadek Karang (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p22, 2023)
In an effort to eradicate rabies, vaccination has been carried out for rabies carriers (HPR), such as dogs, cats and monkeys. Vaccination of dogs in the field has been carried out by the district/city Animal Husbandry Service once a year which is centered on each sub-village and even visits household from door to door. In order to provide a good protection, vaccination coverage is should above 70% of the HPR population at risk. Mother dogs who have antibodies will transfer them to their puppies through the placenta and milk when they give birth. Antibodies transferred from mother to child are called Maternal Antibodies (MA). To find out whether puppies have MA rabies, a study was conducted on puppies at the Beringkit Market, Badung Regency, using a descriptive observation method. The research aims to detect whether the puppies sold at the Beringkit market have maternal antibodies. ELISA test is conducted to measure the antibody from serum sample. A total of 30 serum lample were examined. From the results of the study using, 40% of 30 dog have had protective maternal antibodies (OD value >0.5IU) and 60% have not had protective maternal antibodies.